2017
DOI: 10.1111/ajt.13936
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Donor HLA Antibody Response After Pancreatic Islet Grafting: Characteristics, Risk Factors, and Impact on Graft Function

Abstract: Pancreatic islet grafting restores endogenous insulin production in type 1 diabetic patients, but long-term outcomes remain disappointing as a result of immunological destruction of allogeneic islets. In solid organ transplantation, donor-specific anti-HLA antibodies (DSA) are the first cause of organ failure. This retrospective multicentric study aimed at providing in-depth characterization of DSA response after pancreatic islet grafting, identifying the risk factor for DSA generation and determining the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
(73 reference statements)
1
20
0
Order By: Relevance
“…We read with interest the study by Pouliquen et al for the GRAGIL network (1). This seeks to address the important question of the role of donor-directed HLA antibodies (DSAs) after pancreatic islet transplantation by examining samples from multiple centers.…”
Section: Donor-specific Antibodies-the Devil Is In the Detailmentioning
confidence: 99%
“…We read with interest the study by Pouliquen et al for the GRAGIL network (1). This seeks to address the important question of the role of donor-directed HLA antibodies (DSAs) after pancreatic islet transplantation by examining samples from multiple centers.…”
Section: Donor-specific Antibodies-the Devil Is In the Detailmentioning
confidence: 99%
“…Epitope-based matching has already shown improvement of outcomes in other organs. (9)(10)(11)(12)(13)(14) Some studies have shown that HLA class I and class II MMs with low eplet loads are less likely to induce antibody responses. (15) Recently, Willicombe et al demonstrated that the epitope MM burden predicts the risk of dn-DSA formation in kidney transplantation.…”
mentioning
confidence: 99%
“…In our cohort, onethird of islet graft recipients developed alloantibodies directed against mismatched HLA molecules expressed by the graft. The diversity of the repertoire and the titer of donor-specific antibodies (DSAs) were highly variable, and maintenance immunosuppression appeared to protect against DSA generation (2). Interestingly, and in marked contrast with solid organ transplantation (where antibody-mediated rejection is widely considered the main cause of transplant failure [3]), the appearance of DSAs did not seem to accelerate the rate of islet graft attrition in our cohort (2).…”
Section: Cum Hoc Sed Non Propter Hocmentioning
confidence: 70%
“…The diversity of the repertoire and the titer of donor-specific antibodies (DSAs) were highly variable, and maintenance immunosuppression appeared to protect against DSA generation (2). Interestingly, and in marked contrast with solid organ transplantation (where antibody-mediated rejection is widely considered the main cause of transplant failure [3]), the appearance of DSAs did not seem to accelerate the rate of islet graft attrition in our cohort (2). While our conclusion has since been confirmed in an independent single-center study (4), it is in striking disagreement with a previous report, which found an absolute association between de novo DSA onset and graft loss in five islet recipients (5).…”
Section: Cum Hoc Sed Non Propter Hocmentioning
confidence: 99%